2020
DOI: 10.1038/s41598-020-65491-2
|View full text |Cite
|
Sign up to set email alerts
|

SMRT sequencing revealed to be an effective method for ADTKD-MUC1 diagnosis through follow-up analysis of a Chinese family

Abstract: We reported a large Chinese family diagnosed with autosomal dominant tubulointerstitial kidney disease caused by MUC1 mutation (ADTKD-MUC1). Cytosine duplication within a string of 7 cytosines in the variable-number tandem repeats (VNTR) region of the MUC1 gene was detected by long-read single-molecule real-time (SMRT) sequencing. MUC1 frameshift protein (MUC1fs) was found to be expressed in renal tubules and urinary exfoliated cells by pathological examination. The family, which consisted of 5 generations inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Wang et al. 8 also revealed the usefulness of SMRT sequencing for detecting MUC1 VNTR mutations in a large Chinese family. Nevertheless, owing to their study design, these 2 studies did not determine the detection rate of MUC1 VNTR variants in patients with clinically suspected ADTKD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al. 8 also revealed the usefulness of SMRT sequencing for detecting MUC1 VNTR mutations in a large Chinese family. Nevertheless, owing to their study design, these 2 studies did not determine the detection rate of MUC1 VNTR variants in patients with clinically suspected ADTKD.…”
Section: Discussionmentioning
confidence: 99%
“…7 Wang et al also demonstrated the usefulness of SMRT sequencing for detecting MUC1 VNTR mutations in a large Chinese family. 8 However, owing to their study design, these two studies did not determine the detection rate of MUC1 VNTR variants in patients with clinically suspected ADTKD. In this study, we clarified that the diagnostic rate of MUC1 variants in patients with clinically suspected ADTKD was 18.8%, which may facilitate more accurate probabilities, especially during genetic counseling.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Europe and America showed a varied prevalence of ADTKD-MUC1. ADTKD-MUC1 was reported to be rare in Chinese 23,24 . The clinical manifestations of hereditary cystic kidney disease were hard to distinguish, therefore, suspected ADTKD patient without ADTKD gene mutations may be due to other hereditary kidney diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence reads were aligned to the reference sequence NM_001204286 and analyzed using NextGENE software. The MUC1 mutation positive control was donated by professor Hong Cheng 24 .…”
Section: Screening For Genetic Variants Sanger Sequencing Of the Umomentioning
confidence: 99%